Effects of steel properties on the local buckling response of high strength pipelines subjected to reverse faulting - Liu, Xiaoben; Zhang, Hong; Li, Meng; Xia, Mengying; Zheng, Wei; Wu, Kai; Han, Yinshan (Journal of natural gas science and engineering, 2016)
The reverse fault is one of main threats faced by high strength gas pipelines, for the potential of leading to buckling failure in the pipe. A 3D finite element model was established in this study, in which the pipe was modeled by shell elements and the pipe-soil interaction relationship by spring elements. A suitable equivalent boundary condition is introduced at the ends of the pipe to simulate the remote end and reduce the model dimension. The mechanical behavior of the buckling process of the pipe was studied. 10 high strength pipe steel materials of 3 different APL 5L grades (X80, X90, X100) were taken into consideration to analyze the influences of the yield strength and the strain hardening parameter of the pipe steel material on the buckling behavior. Results show that, when buckling occurs in high strength steel gas pipelines under reverse fault displacement, the Mises stress in the buckling position of the pipe is about 1.1 times the yield strength of the pipe steel. The critical fault displacement and axial stress increase with the increase of the yield strength, and decrease with the increase of the hardening parameter, while both the yield strength and the hardening parameter have a small influence on the critical axial strain. [Display omitted] •Local buckling response of high strength pipelines across reverse faulting has been studied.•Effects of steel properties on critical axial stress and strain have been studied.•Theory analysis has been conducted to illustrate buckle formation.